The resettlement of Vietnamese refugees across Canada over three decades - Feng Hou (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Welcoming 60,000 Southeast Asian refugees in the 1979-80 period has become a celebrated part of Canada's history, but the eventual integration of these refugees into Canadian society has received insufficient attention. This study provides a comprehensive overview of Vietnamese refugees' economic outcomes over the three decades after their arrival. This study also explores how regional contexts contributed to shaping economic outcomes. Based on analyses of the 1981, 1991, and 2001 census and the 2011 National Household Survey, this study finds that adult Vietnamese refugees arrived with little human capital, but they had high employment rates, and over time they closed their initial large earnings gap with other immigrants. Childhood Vietnamese refugees out-performed other childhood immigrants and similar-aged Canadian-born individuals in educational attainment and earnings when they reached adulthood. The geographic region of residence was associated with some large variations in refugees' socioeconomic outcomes; and regional differences in refugees' human capital characteristics, ethnic enclave, and economic conditions played varying roles depending on the outcome measure and length of residence.
Keywords: I32; J15; 330; Canada; earnings; economic integration; employment; poverty; Vietnamese refugees